Genre and Style Interaction in Solutions Staged Ballets of the Nineteenth, Twentieth Centuries - Tatiana PORTNOVA (Astra Salvensis, 2019)
The relevance of this study is determined by the need to create a new scientific approach to conducting an analysis of specific properties of the genre and style in the ballet theater, arising from the theoretical problems of ballet as a scenic genre based on the visual nature of perception. The question is raised about the meaning of the plot, event-related beginning in genres of the considered arts. Based on a number of studies in the field of choreography, the author uses a system-semiotic analysis of a semantic category in dance. In the article the questions concerning the genre and stylistic solutions ballets and dance numbers staged by examples of decisions of the nineteenth, twentieth century, considered the relation of genre and style in the structure of a number of ballet performances. Of all types of expressive dance art tends to be the most figurative. The ratio in the modern dance space pictorial and expressive on the basis of existing dance techniques creates new approaches to understanding and mastering the art of ballet. Thus, research methodology based on the system-comparative analysis of genre elements makes it possible to highlight deep regular contacts between them and expand the understanding of modern dance vocabulary, orienting researchers to the latest integrative approaches to mastering the synthetic nature of the ballet theater.